GC-MS Determination of Major Bioactive Constituents and Anti-oxidative Activities of Aqueous Extracts of Cinnamomum burmannii Blume Stem - A. Akowuah, Gabriel; Ahmad, Mariam; C. Tan, Soo; F. Yam, Mun (Natural Products Journal, The, 2013)
The aim of this study was to determine the major boactive constituents, trans-cinnamic acid and transcinnamaldehyde, and anti-oxidative activities of 50% aqueous methanol and water extracts of Cinnamomum burmannii Blume stem bark. Gas chromatography-mass spectrometry (GC-MS) was used to analyse the extracts. The content of trans-cinnalmadeyde quantified in the 50% aqueous methanol and water extracts were 50.14 μg/mg and 12.83 μg/mg of dry extract, respectively. The content of trans-cinnamic acid quantified in the water extract was 49.7 μg/mg of dry extract. Trans-cinnamic acid was not detected in the 50% aqueous methanol (v/v) extract. The extracts demonstrated in vitro antioxidative effects with the 50% aqueous methanol extract being more potent than the water extract.
Keywords: Cinnamomun burmannii